Analiza poškodb na površini orodja za tlačno litje nosilca iz aluminijeve zlitine AlSi9Cu3 - Kosec, Borut (Strojniški vestnik, 2001)
On the surface of a casting die surface cracks appeared after less than one thousand custing cycles and caused in imprints on AlSi9Cu3 aluminium alloy girder castings. The cracks were revealed and identified by the use of penetrants. They were analysed in detail by the nondestructive metallographic examination by replicas method.
Keywords: orodja livarska; litje tlačno; zlitine Al; analize poškodb; tlačno litje; aluminijeve zlitine; aluminium alloy; orodja; površinske napake